Current situation of the prevention of type 2 diabetes mellitus - Garmendia Lorena, Fausto Aníbal (2022)
Most of aspects of Diabetes Mellitus type 2 (DM2) subject to be prevented are reviewed, to low down the morbi-mortality of this disease under the current circumstances. In a descriptive, transversal study, the aspects and methods to prevent both the development of the disease as well as its chronic manifestations, acute complications and related morbidities are described. It is concluded that effective measures and methods to diminish the prevalence and morbi-mortality of type 2 diabetes mellitus are available under the current circumstances.